2018
DOI: 10.1044/2018_jslhr-h-18-0097
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Measures of N1 Peak Amplitude of the Compound Action Potential in Younger and Older Adults

Abstract: Our results suggest that measurements of AN activity can be robustly and reliably recorded in both younger and older adults using either peak-to-peak or baseline-corrected measurements of the N1 of the CAP. Peak-to-peak measurements yield larger N1 response amplitudes and are the default measurement type for many clinical systems, whereas baseline-corrected measurements are computationally simpler. Furthermore, the relationships between AN activity and stimulus- and participant-related variables were not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
6
21
0
Order By: Relevance
“…Wave I was successfully recorded in all subjects and was found to be reduced in amplitude in the ONH group relative to the YNH group, consistent with the findings of Burkard and Sims (2001) and McClaskey et al. (2018).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Wave I was successfully recorded in all subjects and was found to be reduced in amplitude in the ONH group relative to the YNH group, consistent with the findings of Burkard and Sims (2001) and McClaskey et al. (2018).…”
Section: Discussionsupporting
confidence: 83%
“…Work by Burkard and Sims (2001) has shown that, for a single high click level, the amplitude of Wave I is markedly lower in older listeners with normal hearing or mild hearing loss compared with normal-hearing young adults. Similarly, McClaskey, Dias, Dubno, and Harris (2018) have shown that the amplitude of the compound action potential of the electrocochleographic response, which corresponds to Wave I of the ABR, is smaller in older adults with near-normal hearing than in young adults. The purpose of the present experiment was to extend this finding to measure the ABR in older listeners with near-normal audiometric hearing at two different levels to characterize growth functions, again with a particular focus on the amplitudes of Wave I and Wave V. In summary, the hypothesis of this experiment is that older listeners with near-normal audiometric hearing have reduced Wave I amplitudes, and this is most evidenced by a reduced Wave I/Wave V amplitude ratio.…”
Section: Experiments 1: Abrsmentioning
confidence: 85%
“…Procedures for measuring cochlear potentials with the Sanibel TM electrode are very similar to those used for the TM-Wick electrode. CAP amplitudes measured in response to clicks presented between 80-105 dB peSPL have been reported for several studies that used the Sanibel electrode (Stamper and Johnson, 2015;Harris et al, 2018;McClaskey et al, 2018), and are consistent with the 0.44 µV baseline-to-peak CAP amplitudes of the current study for clicks presented at 90 dB peSPL. These results show that the CAP amplitudes reported for the commercially-available electrode in the current study are consistent with CAP amplitudes obtained in previous studies that used a comparable commercially-available TM electrode.…”
Section: Comparison Of Tm Electrodessupporting
confidence: 90%
“…CAP N1 was smaller in older compared to younger adult human subjects (100 µS click, 110 dB pSPL). C. Amplitude differences in N1 in B were also observed in another group of younger and older adults where age-related differences were observed at signal levels of 110 dB pSPL (* p < 0.001) but not at 80 dB pSPL ( McClaskey, et al., 2018 ), which further suggests that age-related declines in the amplitude of the N1 are level-dependent. …”
Section: Consequences Of Peripheral Declines and Neural Presbyacusismentioning
confidence: 68%
“…In animals, where neural loss can be quantified, a partial loss or dysfunction of IHC synapses, spiral ganglion, or auditory nerve fibers results in reduced maximum amplitudes and shallower slopes of amplitude input-output functions ( Hellstrom and Schmiedt, 1990 ; Nadol, 1997 , Mills and Schmiedt, 2004 , Kujawa and Liberman, 2015 ). Cross-sectional data from humans suggest a similar phenomenon, with older adults showing shallower slopes of Wave I amplitude input-output functions and reduced maximum amplitudes compared to younger adults ( Konrad-Martin, et al., 2012 ; McClaskey, et al., 2018 ). Similar age-related differences in auditory nerve function are observed in rodents, as shown in Figure 9 .…”
Section: Consequences Of Peripheral Declines and Neural Presbyacusismentioning
confidence: 87%